E-JASBIO: Development of Canva-Based Electronic Module to Enhance Environmental Awareness for Students - Nukhbatul Bidayati Haka; Sagita Nia Marfuah; Anisa Oktina Sari Pratama; Nur Hidayah; Hardiyansyah Masya; Yuni Astuti (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This research aims to develop an electronic module based on Canva to enhance environmental awareness among seventh-grade students. The module development process utilized the Research and Development (R&D) approach with the Borg and Gall development model. The development steps include field studies, planning, initial product development, limited testing, product revision, extensive testing, effectiveness evaluation, and final product revision. The E-JASBIO module contains materials on environmental pollution, presented in an engaging format with the integration of Quranic verses. The validation results from experts indicate a high level of suitability, with media experts rating it at 81%, material experts at 92%, and language experts at 88%. Field testing involving limited participants showed positive responses from teachers (78%) and students (80%), indicating the module's effectiveness. In conclusion, the E-JASBIO module is deemed highly suitable and effective in enhancing environmental awareness among seventh-grade students, with its engaging content and integration of multimedia elements contributing to its success.